(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Odpowiedzialność karna nie zawsze wiąże się przy tym z realizacją przez sprawcę wszystkich znamion czynu zabronionego jego własnym zachowaniem. Wprawdzie nawet wówczas sprawca ponosi odpowiedzialność za własne (a nie: cudze) działanie lub zaniechanie. Jednakże odpowiedzialność ta powiązana jest z zachowaniem, którym reguły postępowania względem chronionego dobra narusza bezpośrednio inna osoba niż sprawca. Zachowanie sprawcze może przyjąć formę działania lub zaniechania w różnym układzie personalnym, co znajduje wyraz w różnym ukształtowaniu form sprawstwa w art. 18§1 kk. Ponadto konstruując typy czynów zabronionych ustawodawca posługuje się niekiedy znamionami wskazującymi wyraźnie na ścisłe powiązanie zakresu odpowiedzialności karnej sprawcy z zachowaniem innych osób, jak: „kto dopuszcza do...” czy „kto bierze udział w...” Wreszcie – co stanowi przedmiot analizy w niniejszym artykule – nawet pomimo braku wyraźnego wskazania w ustawie na zasadność przypisania sprawcy odpowiedzialności za naruszenie reguł postępowania z dobrem prawnym przez inny podmiot, sam proces przypisywania odpowiedzialności karnej, poprzez powiązanie jej z formalnym lub faktycznym zakresem obowiązków sprawcy, może powodować przypisanie mu odpowiedzialności (za zaniechanie w razie samego faktu zaistnienia określonego stanu rzeczy). The issue raised in the article applies to determine whether it is possible to exempt from criminal liability of the person who sent to perform some dutiesm associated with the law of its function performed by another person in the event of such failure to comply with these obligations by the person performing them, that results in the fulfillment of the criminal offense. The relevance of issues raised due to the fact of being bound by the law of some functions such a wide range of duties that the reliable performance of all these duties by one person which performs this function, is not possible, which forces the transfer of some tasks to other people. No transfer in the wake of the criminal responsibility can lead to the situation where the person liable, despite exercising due diligence in the exercise of its functions, which is expressed in the transfer of some of responsibilities, which is not able to perform on his own to other competent bodies, can still be held criminally liable for their improper performance. This situation can cause that criminal liability would be in place of strictly individual responsibility, based on the guilt of the individual, to whom the requirements of a specific behavior were made, foreign to criminal liability responsibility for risk. It should be noted that in some cases legal regulations explicitly exclude the possibility of exemption from liability by the transfer of certain tasks to a third party. Usually, however, there is no regulation in this area which allows for the analysis of the issues raised based on the assumptions underlying the criminal law. The article analyzes the problem based on examples of regulation in civil law with particular emphasis on tort liability, commercial law, construction law, labor law, accounting law and pharmaceutical law. The conclusions indicated the extent to which effective transfer of responsibilities to another person or just entrust another person to perform certain duties assigned to the function of the person liable, may modify the scope of the criminal responsibility of the entity. The raised issue of delegation of duties tested for formal reasons associated with this activity as well as one of the most important bases of criminal responsibility, which is a violation of the prudent (rational) behavior. Admissibility of delegating a part of one’s duties to another entity does not eliminate the problem of criminal responsibility for failure to comply with them by the required person that whether wasn’t diligent enough in choosing an entity to whom he passed his duties, or did not show even a small range of interest to the actual and proper execution of these duties by this entity.